STABILITAS FISIKA DAN KIMIA REKRISTAL DAN DISPERSI PADAT PIROKSIKAM-PEG 6000 - Binarjo, Annas (Pharmaciana, 2015)
It is hoped that solid dispersion and recrystalization can solve the problem of low solubility of piroxicam.  Metastable polymorph or amorph state can be formed in solid dispersion and recrystalization preparation, leading to a better dissolution. During storage, the metastable polymorph or amorph will be changed to stable crystal, so that the dissolution will be decreased (physical instability), beside that the increasing of solubility also trigger the higher rate of decomposition (chemical instability).  This research was purposed to reveal these two instability. The research was began by preparing recrystal of piroxicam (R) and solid dispersion piroxicam-PEG 6000 (DP) by solvent method using aseton.  These preparate were stored in room temperature (25oC). The dissolution was tested after 1, 2, 3, and 4 month of storage, using dissolution efficiency for 60 minutes (DE60) as parameter, and also the drug content in bulk preparate was determined. The result showed that recrystalization and solid dispersion preparation did not decrease  the piroxicam content.  During storage, the DE60 and piroxicam content in R and DP were not changed (p>0.05). It could be concluded that R and DP prepared had a stable dissolution and purity.